Crosstalk Suppressed High Efficient Mode-Selective Four-Wave Mixing Through Tailoring Waveguide Geometry - Jiabi Xiong; Yu Yu; Weili Yang; Chunlei Sun; Xinliang Zhang (IEEE Photonics Journal, 2019)
We propose and demonstrate improved and accurate design criteria for mode-selective nonlinear waveguides, using a complete multimode theoretical model. Being different from previously reported schemes where only the cross section was considered, the nonlinear conversion efficiency can be further enhanced in the proposed scheme by means of elaborately designing both the waveguide length and cross section. Furthermore, the modal crosstalks introduced by the intermode nonlinear processes are thoroughly discussed and significantly suppressed. A two-mode nonlinear circuit using asymmetric directional coupler based multiplexer/de-multiplexer and an optimized multimode waveguide is fabricated for demonstration, utilizing a silicon integrated platform. Experimental results show that the highest conversion efficiencies of fundamental transverse electric and first order transverse electric modes are -20.44 and -23.15 dB, respectively, with nonlinear crosstalks less than -19 dB.